Western nightmares: Manifest Destiny and the representation of genocide in weird fiction. Issue 2 (1st December 2017) - Manea, Dragoş
This article focuses on the representation of genocide in Manifest Destiny (Dingess 2013–present), a comic book series loosely based on the 1804–06 Lewis and Clark expedition, replete with fantastical creatures, strange habitats and superhuman acts of heroism. The graphic narrative, published by Skybound/Image Comics, with art by Matthew Roberts and Owen Gieni, tells the story of the Corps of Discovery as they explore a quasi-mythical uncharted land, on the orders of President Jefferson. Their mission is to map and tame the newly purchased Louisiana Territory and prepare it for American settlers by killing the myriad monsters that still populate the strange land (including buffalotaurs, gigantic frogs, sentient anthropomorphic birds and a plant that infects humans and animals, turning their insides to plant-like material and robbing them of their will). By analysing it as a work of weird fiction, I explore how the presence of monstrous creatures creates a number of effects, from the horrific to the unsettling, outlines the killers' awareness of the moral ambiguity of their actions and encourages readers' identification with genocide perpetrators. The series, I argue, is grounded upon a formal realism that makes it highly effective in depicting scenes of weird fiction, whose defamiliarizing effect can rely on combining conventional, highly realistic settings, characters or tableaux with strange elements that pervert and yet do not render them unrecognizable. In conversation with critics and writers such as Ian Dawe, Darja Malcolm-Clarke, Simon Spiegel and Ann and Jeff VanderMeer, I attempt to explore the formal strategies adopted by the series in order to create scenes of weird fiction and their ethical implications.